Respuesta :

2x - 2y = -12

4x - 7y = -15

Multiply the first equation by -2 to make the 2x the opposite of 4x:

2x - 2y = -12 x -2 = -4x + 4y = 24

Now add this to the second equation:

-4x + 4y = 24 + 4x - 7y = -15:

-3y = 9

Divide both sides by -3

y = 9 / -3

y = -3

Now you have Y, replace y in one of the equations and solve for x:

2x - 2(-3) = -12

2x +6 = -12

Subtract 6 from both sides:

2x = -18

Divide both sides by 2:

x = -18 /2

X = -9

Check:

2(-9) - 2(-3) = -12

-18 + 6 = -12 TRUE

4(-9) - 7(-3) = -15

-36 +21 = -15 TRUE

X = -9, y = -3

(-9,-3)